THE ROLE OF OPPOSITION IN THE FORMATION OF THE ORONIM OF BAYSUN DISTRICT (World Bulletin of Social Sciences, 2024)
In this article, observation of the state of opposition in the composition of Baysun district oronims is noted and an opinion is expressed about oronims that are examples of opposition.